计算:3√x+5√y-2√x√y-√x (2)√2-√3/2+√2/3-√3/5+3√3+2√2 (3) √6-√12+√18-√24-√32

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/30 03:35:20
计算:3√x+5√y-2√x√y-√x (2)√2-√3/2+√2/3-√3/5+3√3+2√2 (3) √6-√12+√18-√24-√32
x){nuecV)5,CAHH8F 1g g aad -@l#j#"}:ۨ_`g3cX]A5XXg@Lj P}( J `P-Xvc5F`KtJ!?r[iŋ募S]QWZd``>6(y"D㲦g<t>dgǓf=i'ؿu:6yvK

计算:3√x+5√y-2√x√y-√x (2)√2-√3/2+√2/3-√3/5+3√3+2√2 (3) √6-√12+√18-√24-√32
计算:3√x+5√y-2√x√y-√x (2)√2-√3/2+√2/3-√3/5+3√3+2√2 (3) √6-√12+√18-√24-√32

计算:3√x+5√y-2√x√y-√x (2)√2-√3/2+√2/3-√3/5+3√3+2√2 (3) √6-√12+√18-√24-√32
3√x+5√y-2√x√y-√x
=2√x+5√y-2√xy;
(2)√2-√3/2+√2/3-√3/5+3√3+2√2
=√2+√2/3+2√2-√3/2-√3/5+3√3
=10√2/3+23√3/3;
(3) √6-√12+√18-√24-√32
=√6-2√3+3√2-2√6-4√2
=-√6-2√3-√2;
很高兴为您解答,skyhunter002为您答疑解惑
如果本题有什么不明白可以追问,